The brokerage institution and the development of agricultural markets: New evidence from Ethiopia - Quattri, Maria; Ozanne, Adam; Beyene, Seneshaw Tamru (International Food Policy Research Institute, 2012)
Recognition that policies aimed at ‘getting prices right’ in less-developed countries have not been successful due to incomplete markets has spurred a new wave of reforms aimed instead at ‘getting markets and institutions right’. Previous studies of this policy shift have documented the potentially crucial role played by the brokerage institution in crop commercialization. However, few have investigated the factors that influence wholesalers’ decisions regarding their use of brokers. Results from a primary survey with traders show that brokerage services are particularly valuable for wholesalers who lack social capital and storage capacity, who are based in areas with low population density, and who trade at a distance, especially when roads are not asphalt. Buyers in drought-prone domains rely on brokers more for their long-distance purchases, while sellers in moisture-reliable domains employ brokers more for their long-distance sales. These results provide useful indications regarding where and how the recent formalization of brokerage functions through the Ethiopian Commodity Exchange (ECX) could be most beneficial for the functioning of Ethiopian agricultural markets.